2020
DOI: 10.1186/s12874-020-01164-y
|View full text |Cite
|
Sign up to set email alerts
|

Combining the theory of change and realist evaluation approaches to elicit an initial program theory of the MomConnect program in South Africa

Abstract: Background One of the Sustainable Development Goals is to reduce the global maternal mortality ratio to less than 70 per 100,000 live births by 2030. In South Africa, the flagship National Department of Health MomConnect program was launched in 2014 to strengthen the quality of maternal and child health (MCH) services and improve mortality outcomes. MomConnect was rapidly rolled out with a limited understanding of how and why the program was expected to work even though studies had shown the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0
12

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 42 publications
1
16
0
12
Order By: Relevance
“…Moreover, our model is supported by a systematic review by Aker et al that found that users’ perceived platform quality, perceived satisfaction of care, perceived quality interaction and outcomes, influence users’ uptake of mHealth for health care [ 69 ]. Our findings are supported by a realist-informed document review that identified empowerment, perceived quality of MCH care, encouragement, motivation, and knowledge acquisition as the main mechanisms driving the implementation and uptake of MCH care through the MomConnect program [ 70 ].…”
Section: Discussionsupporting
confidence: 64%
“…Moreover, our model is supported by a systematic review by Aker et al that found that users’ perceived platform quality, perceived satisfaction of care, perceived quality interaction and outcomes, influence users’ uptake of mHealth for health care [ 69 ]. Our findings are supported by a realist-informed document review that identified empowerment, perceived quality of MCH care, encouragement, motivation, and knowledge acquisition as the main mechanisms driving the implementation and uptake of MCH care through the MomConnect program [ 70 ].…”
Section: Discussionsupporting
confidence: 64%
“…They identi ed other dimensions, such as system reliability, privacy, availability, adaptability, e ciency, assurance, responsiveness, functional and emotional bene ts to in uence the uptake of mHealth interventions. Our ndings are supported by a realist-informed document review that identi ed empowerment, perceived quality of MCH care, encouragement, motivation, and knowledge acquisition as the main mechanisms driving the implementation and uptake of MCH care through the MomConnect programme [68].…”
Section: Discussionmentioning
confidence: 52%
“…Theory of change approaches and realist evaluation are increasingly used in research and evaluation of health services and medical education because they rely on theory to drive the evaluation of complex interventions 16–19 . Stemming from different ontologies, these two approaches provide steps to consider context in the implementation and evaluation of complex interventions.…”
Section: Methodsmentioning
confidence: 99%
“…Stemming from different ontologies, these two approaches provide steps to consider context in the implementation and evaluation of complex interventions. Theory of change evaluations tend to focus on the how change occurs during implementation of a complex intervention (implementation theory) while realist evaluations are interested in the why (programme theory) 18–20 . A combined theory of change/realist evaluation approach can produce a more nuanced output by integrating the respective methods sequentially 20,21 .…”
Section: Methodsmentioning
confidence: 99%